2001
DOI: 10.1191/095968301667179797
|View full text |Cite
|
Sign up to set email alerts
|

Late-Holocene (post-4000 years BP) coastal dune development in Northumberland, northeast England

Abstract: The recent environmental history of coastal dune systems in Northumberland, northeast England, has been examined using geomorphological, stratigraphical and sedimentological techniques linked to radiocarbon and infrared-stimulated luminescence (IRSL) dating. Stratigraphies were determined from 22 vibracores and three sections, and dune chronology was based on 28 14 C dates, from peat and soil organic horizons, and 26 IRSL dates on K-feldspar grains from within sand layers. Almost all dune systems are associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
83
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 24 publications
2
83
1
Order By: Relevance
“…In the results presented, the first hiatus was found at 2100 BC, which appears in both foredune successions and correlates with a general climatic shift at 2200 BC in the North Atlantic (Bond et al, 1997; McDermott et al, 2001) and a phase of aeolian activity, which was found by Clemmensen et al (2001aClemmensen et al ( , 2009) and Pedersen and Clemmensen (2005) in Jutland (Denmark) furthermore by Wilson et al (2001) and Sommerville et al (2007) in Great Britain. The LIAtype event at 900 BC is also found in our sediment records.…”
Section: Foredune Plain Evolution and Aeolian Sand Movementmentioning
confidence: 53%
See 1 more Smart Citation
“…In the results presented, the first hiatus was found at 2100 BC, which appears in both foredune successions and correlates with a general climatic shift at 2200 BC in the North Atlantic (Bond et al, 1997; McDermott et al, 2001) and a phase of aeolian activity, which was found by Clemmensen et al (2001aClemmensen et al ( , 2009) and Pedersen and Clemmensen (2005) in Jutland (Denmark) furthermore by Wilson et al (2001) and Sommerville et al (2007) in Great Britain. The LIAtype event at 900 BC is also found in our sediment records.…”
Section: Foredune Plain Evolution and Aeolian Sand Movementmentioning
confidence: 53%
“…8). Wilson et al (2001) also found evidence for coastal dune development in Northumberland (NE England, Fig. 8) within cooling (LIA-type) events (at~2200 BC, 700 BC,~600 AD); however, their chronology of aeolian sand movement is less robust because it was based on the indirect radiocarbon ages.…”
Section: Foredune Plain Evolution and Aeolian Sand Movementmentioning
confidence: 91%
“…In the context of LIA conditions in the North Sea basin, initiation of dune building has been perceived as a response to the generally regressive sea-levels during the LIA cooling phase causing a lowering of wave base and an associated increased onshore transport of sand across the shoreface (Orford et al, 2000;Wilson et al, 2001;Orford, 2005), producing both 'wide expanses' of (intertidal) beach laid bare for aeolian action (Christiansen et al, 1990) and accommodation space beyond the regressing high-tide positions. In support of this perspective, sea-level during the LIA may have been 0.5 m lower, or more, compared to the present day in the North Sea region (Rohde, 1978;Lamb, 1991;Behre, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…AD 1750) (Lamb, 1991;Jö nsson, 1994). However, studies of coastal dunefield development in many parts of northwest Europe have added to our knowledge of past storminess variations (Pye and Neal, 1994;Wilson et al, 2001;Clemmensen et al, 2001c;Clarke et al, 2002;Wilson, 2002;Wilson et al, 2004).…”
Section: Introductionmentioning
confidence: 99%